Coopetition-based open-innovation and innovation performance: Role of trust and dependency evidence from Malaysian high-tech SMEs - Waseem Ul Hameed; Farrukh Naveed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
In a highly competitive environment, the phenomenon of coopetition is emerging rapidly among various firms as well as markets which is significant to enhance firm's open innovation performance (FOIP). However, Malaysian High-Tech SMEs are unable to develop a well-managed coopetition mechanism which influence negatively on open innovation (OI) performance. To address this problem, the objective of this study is to investigate the effect of coopetition-based OI on the FOIP. To achieve this objective, a survey was conducted by using cross-sectional research design. Managerial employees of Malaysian high-tech SMEs were selected as the ultimate respondents of this study. While analyzing the data through PLS-SEM, it is revealed that coopetition has major contribution to enhance FOIP. Likewise, it is highlighted that the role of trust and dependency is crucial to develop a good coopetition platform. The study contributed in the body of literature by investigating the mediating role of trust and dependency to enhance the positive effect of coopetition based OI on FOIP, particularly in Malaysian high-tech SMEs. Thus, the current study has major importance for Malaysian high-tech SMEs to look on the vital factors to expedite coopetition and innovation activities.
Keywords: 330; coopetition; open innovation; firm performance; trust; dependency; high-tech SMEs